2009
DOI: 10.5713/ajas.2009.80298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Butyric Acid on Performance, Gastrointestinal Tract Health and Carcass Characteristics in Broiler Chickens

Abstract: An experiment was conducted to study the effect of graded levels of butyric acid (butyrate) on performance, gastrointestinal tract health and carcass characteristics in young broiler chickens. Control starter (0-3 wk) and finisher (4-5 wk) diets were formulated to contain 2,900 kcal ME/kg and 22% CP, and 3,000 kcal ME/kg and 20% CP, respectively. Subsequently, four other experimental diets were formulated to contain 0.05% antibiotic (furazolidone) or 0.2, 0.4 and 0.6% butyric acid. Each diet was fed at random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
3
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 20 publications
11
131
3
12
Order By: Relevance
“…The organic acids eliminate the coliforms from the gastrointestinal tract by reducing the pH, which is unsuitable for the multiplication of the acid-intolerant species such as E. coli and Salmonella (Panda et al, 2009). Our results are in line with Hassen (2011); Park (2011), who stated that total salmonella and E. coli counts were significantly affected by organic acid.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 82%
“…The organic acids eliminate the coliforms from the gastrointestinal tract by reducing the pH, which is unsuitable for the multiplication of the acid-intolerant species such as E. coli and Salmonella (Panda et al, 2009). Our results are in line with Hassen (2011); Park (2011), who stated that total salmonella and E. coli counts were significantly affected by organic acid.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 82%
“…Adil et al (2010) reported that dietary butyric acid (3% application rate) significantly increased the villus height in the duodenum and jejunum only. Similarly, many researchers have described the beneficial effect of dietary sodium butyrate on villi height and crypt depth in broilers at different phases of their growth (Antongiovanni et al, 2007;Mallo et al, 2012;Panda et al, 2009;Sayrafi et al, 2011;Smulikowska et al, 2009). On the contrary, some researchers did not find any effect of dietary sodium butyrate on villi height and crypt depth (Leeson et al, 2005).…”
Section: Gut Morphologymentioning
confidence: 90%
“…(Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Similarly, butyric acid enhanced the weight gain and FCR (Panda et al, 2009). Likewise, partially protected and microencapsulated sodium butyrate positively affected the performance of broilers during the grower and finisher periods (Mallo et al, 2010;Zou et al, 2010a).…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 99%
“…Similarly, serum triglyceride level was also found to be reduced when BAG was supplemented in broiler ration at 0.2 ( Jang, 2011;Mansoub, 2011a) and BA at 0.25 % (Dehghani-Tafti and Jahanian, 2016). Addition of 0.6 (Panda et al, 2009), 0.3 % BA (Lakshmi and Sunder, 2015) in broiler chicken reduced the abdominal fat. While, it was not influenced by inclusion of 0.04 % microencapsulated SB (Zhang et al, 2011b), 0.3 % protected BA (Mahdavi andTorki, 2009), 0.25 (Aghazadeh andYazdi, 2012) and 0.2 % BAG ( Jang, 2011).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…eFFect on ph oF intestinAl digestA Supplementation of 0.6% BA reduces the pH of gastrointestinal segments such as crop, proventriculus, gizzard and duodenum (Panda et al, 2009), whereas, ileal pH was not altered by addition of 0.3 % BAG (Mahdavi and Torki, 2009) and 0.03% coated SB (Czerwinski et al, 2012) in broiler ration. Similar comparable caecal pH was also recorded when 0.03 % fat coated SB (Smulikowska et al, 2009) and 0.1 % SB together with essential oil (Cerisuelo et al, 2014) were used in broiler ration.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%